Modern power electronics evolution, technology, and applications - Bose, Bimal K. (IEEE Press, 1992)
Provides the latest techniques and energy-saving applications for working with power semiconductor devices, ac-dc converters, ac-ac converters, dc-dc converters, dc-ac converters. PWM methods, and converter applications. This book starts with a very comprehensive tutorial section which reviews state-of-the-art power electronics technology, integrating power semiconductor devices, different classes of converter topologies, PWM techniques, and key power electronics applications.